Coix Seed-Based Milk Fermented With Limosilactobacillus reuteri Improves Lipid Metabolism and Gut Microbiota in Mice Fed With a High-Fat Diet - Yang, Zhoujie; Zhu, Xiaoli; Wen, Anyan; Ran, Jingqi; Qin, Likang; Zhu, Yi (Frontiers in Nutrition, 2022)
The aim of this study was to investigate the effects of coix seed-based milk (CSM) fermented with Limosi-lactobacillus reuteri (L. reuteri) on dyslipidemia and the composition of the intestinal microbiota in high fat diet (HFD)-fed mice. Changes in the body weight, serum lipid levels, activities of hepatic oxidative stress factors, expression of lipid-related genes, and composition of the intestinal microbiota of HFD-fed mice after sup-plementation with CSM were determined. The results showed that intake of CSM reduced the body weight gain as well as serum total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C) levels, and increased the high-density lipoprotein cholesterol (HDL-C) levels in the mice. Meanwhile, sup-plementation with CSM increased the activities of superoxide dismutase (SOD), catalase (CAT), and gluta-thione peroxidase (GSH-Px) in the liver and decreased the production of malondialdehyde (MDA). Moreover, CSM also promoted reductions in the expression of lipid biosynthesis-related genes in the liver, effectively preventing steatosis of the liver. The 16S rRNA sequencing of the intestinal microbiota showed that CSM regulated the structure of the gut microbiota at different taxonomic levels. CSM increased the abundance of beneficial microorganisms, such as Muribaculaceae, Lachnospiraceae, Ruminococcaceae, and Akkermansia and decreased the abundance of Desulfovibrionaceae, which are associated with inflammation. Therefore, CSM might serve as a novel and promising dietary supplement for ameliorating hyperlipidemia and intestinal microbiota disorders caused by HFDs.